SFBC with pre-filtering technique for DL TDD MC-CDMA systems in high data rate context - Silva, Adão
This paper deals with downlink space-frequency block coding with a pre-filtering technique for time division duplex MC-CDMA. We consider the use of antenna arrays at the base station (BS) and a single antenna at the mobile terminal (MT). The space-frequency block codes allow that the spatial diversity be efficiently exploited and the linear multi-user pre-filtering technique allows to format the transmitted signals so that the multiple access interference (MAI) and channel distortions at mobile terminals are completely removed. The aim of this technique is to transfer the most computational complexity from MT to the BS, keeping the first one at very low complexity. Simulations results are carried out in high data rate scenarios with the channel turbo code specified for the current UMTS system, to demonstrate the effectiveness of the proposed multi-user pre-filtering algorithm with SFBC. © 2005 IEEE.